(untitled) (Bioagro, 2020)
Globally, much effort is being made to increase water productivity in agriculture because water supplies are under pressure from other users and are being affected by climate change. The objective of this study was to evaluate, in the stevia crop, a strategy that achieves an increase in water productivity without reducing the yield of the plant. We evaluated the effect of four treatments of deficit irrigation: 25, 50, 75 and 100 % of the crop evapotranspiration (ETc), combined with irrigation without deficit, on changes in soil water content, crop yield and water use efficiency. In the treatment with 50 % ETc, the strategy prevented plant water stress and permitted an efficient use of water by the crop which implied an important saving of the water resource.